PERAN ORANG TUA DALAM MEMBIMBING KARAKTER ANAK REMAJA USIA 12-15 TAHUN DI GEREJA BETHEL INDONESIA TABGHA TANJUNG PIAYU BATAM - Johannes Hutabarat; Steven Lin; Agustina Sinaga (JURNAL IMPARTA, 2024)
Parents do not yet have an understanding of the role of parents in guiding the character of teenagers aged 12-15 years. The character of teenagers at GBI Tabgha Tanjung Piayu Batam has challenges because there are still those involved in racing, the temptation to smoke, drink alcohol, the social interactions of school children who often tempt them not to take part in church activities, like to go against their parents, have a bad temper and are stubborn. . Parents lack communication with teenage children at GBI Tabgha Tanjung Piayu Batam so that there is a breakdown in the relationship between parents and children and the children's character is not formed from a positive environment. The character of teenagers at GBI Tabgha Tanjung Piayu Batam has challenges because some are still involved in racing, tempted to smoke, drink alcohol. This research aims to find out the extent of the benefits of the role of parents in guiding the character of teenagers aged 12-15 years at Bethel Indonesia Tabgha Church Tanjung Piayu Batam. The role of parents is realized through regular and personal guidance regarding positive and negative things that should be avoided or done. Parents play a role in forming the spiritual maturity of their teenagers based on God's Word so that in the future teenagers will become individuals who are strong and sturdy in their faith and fear of God. This research uses qualitative methods and the informants in this research are five parents whose data can be collected from interviews. The results of the research found that church worship is very useful and proven to develop the character of teenagers. Parents often do not provide space for teenagers to talk about their feelings, problems or worries. A lack of open communication can make children feel unheard or unappreciated. Guiding the character of teenagers, especially parents, is very important in forming a family environment that is harmonious, full of love and understanding for children